DUKUNGAN SUAMI DENGAN SIKAP IBU HAMIL TRIMESTER III DALAM PEMBERIAN ASI EKSKLUSIF - Silvia Ari Agustina; Muftiyatur Rohmah (Oksitosin : Jurnal Ilmiah Kebidanan, 2018)
Breast milk is very beneficial for babies, mothers, families, countries and the earth, so every mother is encouraged to do breastfeeding to their babies. The lowest coverage of exclusive breastfeeding in Gunungkidul District is Girisubo Health Center as much as 32.8%. Many factors influence the low coverage of exclusive breastfeeding, one of them is the support of the family especially the husband. Support from the nearest person (husband) is important in the success of exclusive breastfeeding. Objective this study to Know Relationship between Husband’s Support and woman’s attitude in their third trimester towards Exclusive Breastfeeding at Public Health Center of Girisubo Gunung Kidul. This study types was correlational analytic research with cross sectional study design. Sampling technique used purposive sampling with a large sample of 86 trimester pregnant women 3 who had a husband and live together. Data collection used closed questionnaires with Likert scale. Data analysis used chi square test. This research showed that Husband’s support in exclusive breastfeeding majority in less than 46 respondents (53,5%). Likewise with the attitude of pregnant women in giving the majority of the milk is also negative by 57%. The result of cross tabulation of husband support is negative, mother's attitude in giving ASI 32 fall in negative category, whereas the husband/s support is positive, negative pregnant woman attitude only 17. Result bivariate analysis is known that p value = 0,011, there is relationship between husband support with attitude of pregnant mother with OR value as much as 3,092. It can be concluded that there is a statistically significant relationship between the husband’s support and the attitude of the expectant mother. The husband's positive support to the wife, raises 3 positive attitudes of TM III pregnant women in exclusive breastfeeding. Keywords: Attitude, Support, Exclusive Breast Milk ABSTRAK ASI sangat bermanfaat baik bagi bayi, ibu, keluarga, negara serta bumi, sehingga setiap ibu dianjurkan untuk memberikan ASI. Puskesmas Girisubo mempunyai cakupan pemberian ASI eksklusif terendah di wilayah Kabupaten Gunungkidul yaitu sebanyak 32,8%. Rendahnya cakupan dapat dipengaruhi banyak faktor, salah satunya adalah dukungan dari keluarga khususnya suami. Dukungan dari suami atau keluarga sangat berperan dalam keberhasilan pemberian ASI eksklusif. Tujuan dari peneitian ini adalah mengetahui korelasi dukungan suami dengan sikap Ibu Hamil Trimester III dalam Pemberian ASI Eksklusif di Puskesmas Girisubo Gunung Kidul. Jenis penelitian analitik korelasi dengan desain penelitian cross sectional. Teknik sampling menggunakan purposive sampling. Besar sampel yang digunakan sebanyak 86 ibu hamil trimester 3 yang memiliki suami dan tinggal bersama. Pengumpulan data menggunakan kuesioner tertutup dengan skala Likert. Analisis data menggunakan uji chi square. Hasil penelitian ini adalah Dukungan suami kepada istri dalam memberikan ASI eksklusif mayoritas negatif sebanyak 46 responden (53,5%). Begitu pula dengan sikap ibu hamil dalam memberikan ASI mayoritas juga negatif sebesar 57%. Hasil tabulasi silang dukungan suami yang negatif, sikap ibu hamil TM III dalam memberikan ASI 32 masuk dalam kategori negatif, sedangkan jika dukungan suami yang positif, sikap ibu hamil yang negatif hanya 17. Hasil analisis bivariat menunjukkan nilai p = 0,011, ada korelasi yang signifikan antara dukungan suami dengan sikap ibu hamil dengan nilai OR diketahui 3,092. Dapat disimpulkan bahwa terdapat korelasi yang signifikan secara statistik antara dukungan suami dengan sikap ibu hamil. Dukungan positif suami kepada istri, meningkatkan 3 kali sikap positif ibu hamil TM III dalam pemberian ASI Eksklusif. Kata kunci: Sikap, Dukungan, ASI Eksklusif